The Effect Of Flipped Classroom On Studentsâ€™ Reading Comprehension - Herlindayana, Herlindayana; Sahlan, Sahlan; Alberth, Alberth (Halu Oleo University, 2017)
The Flipped classroom is an educational model in which the standard lecture and homework elements of a courseÂ are â€œreversedâ€ or â€œflippedâ€ in that which is traditionally done in class is now done at home, and that which is traditionally done as homework is now completed in class. This study aimed to investigate the effect of a flipped classroom on students reading comprehension and to examine studentsâ€™ perception about the flipped classroom. This study employed a pre-experimental mixed method design combining both quantitative and qualitative designs. The study was conducted at SMA Kartika Â XX-2 Â Kendari,Â involving 32Â students. Instruments of the study were reading test and questionnaires with 5 open-ended questions. Data of the present study were acquired from pre-test, post-test and questionnaires. Results of the study found that there was a significant positive effect of flipped classroom on studentsâ€™ reading comprehension, p (0.000) < 0.05. The effect size was 1.27887. What is more, the majority of the students reported that flipped classroom impacted positively on their learning and learning experience